2021
DOI: 10.3390/ijerph18020687
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hand-Washing Facilities with Water and Soap on Diarrhea Incidence among Children under Five Years in Lao People’s Democratic Republic: A Cross-Sectional Study

Abstract: Diarrhea is a leading cause of death among children under five (U5) in Lao People’s Democratic Republic (PDR). This study assessed the association between the presence of household hand-washing facilities with water and soap and diarrhea episodes among children U5 in Lao PDR. Data from the Lao Social Indicator Survey II were used. The outcome variable was diarrhea episodes in the two weeks preceding the survey. The main predictor variable was the presence of household hand-washing facilities with or without wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 27 publications
(19 reference statements)
1
7
0
Order By: Relevance
“… 2 , 24 , 25 Handwashing with pure soap, on the other hand, is efficient at eliminating harmful microbes. 21 - 23 According to the current meta-analysis study, maternal hygiene intervention should result in a significant reduction in the risk of diarrheal disease in children under the age of 5 years old. 26 HWWS reduces respiratory and skin infections, including trachoma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 24 , 25 Handwashing with pure soap, on the other hand, is efficient at eliminating harmful microbes. 21 - 23 According to the current meta-analysis study, maternal hygiene intervention should result in a significant reduction in the risk of diarrheal disease in children under the age of 5 years old. 26 HWWS reduces respiratory and skin infections, including trachoma.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 From hand hygiene maintaining methods hand washing with soap and water (HWWS) is considered the most cost-effective method to prevent the spread of the microrganisms. [21][22][23] Washing hands with soap and water at important recommended times (after defecation, cleaning the child's buttock who had defecated, before cooking, before eating, and before feeding the child) is the most effective method to prevent infections. 2,24,25 Handwashing with pure soap, on the other hand, is efficient at eliminating harmful microbes.…”
Section: Introductionmentioning
confidence: 99%
“…The main finding of the present study was that potential risk factors for the reported common health problems were often prevalent in the study villages. The possible risk factors for diarrhea including childhood diarrhea found in the survey were not washing hands with soap, open defecation, not boiling drinking water, not exclusively breastfeeding, the absence of garbage management system and the presence of animal feces on the village ground [ 22 24 ]. Likewise, the possible risk factor for malaria found in the survey was not using a bed net when sleeping in the forest [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Designing toilets in a way that facilitates hygienic behavior may help prevent diarrhea. As in the study conducted in Laos, providing soap at handwashing facilities and making it available may help reduce the risk of diarrhea [ 52 ]. In order to reduce the burden of diarrheal diseases more effectively, community-wide sanitation can be introduced in addition to household-level sanitation [ 53 ].…”
Section: Discussionmentioning
confidence: 99%